The Abnormal Pap Smear: A Rationale for Follow Up - Toews, H. A. (1983)
Cervical intraepithelial neoplasia (CIN) is readily identifiable by cytology, so theoretically, most cases of invasive carcinoma should be preventable. Risk factors for carcinoma of the cervix are related to sexual activity, therefore screening should be similarly related. All women should have routine annual cytology as soon as they are sexually active. The high risk male partner should also be considered when taking a history. Those with moderately atypical smears or higher should be referred for further colposcopic evaluation. Good quality cytology will reduce the incidence of false negative smears. Some cases of CIN progress, some remain static, some regress. Colposcopy is valuable in assessing cervical changes; cone biopsy should be required only when colposcopy is inconclusive, or invasion is suspected. Sampling errors in cytology account for the majority of false negative results.